Internal Displacement in Nigeria: Causes, Effects and Prevention - Adeola Oluwafunke Adeleye (Budapest International Research and Critics University, 2023)
According to the findings of this research, the phenomenon of internal displacement in Nigeria is a substantial problem that can be traced back to a wide range of causes, such as armed conflict, community violence, and natural disasters. The repercussions of internal displacement are widespread and encompass a variety of negative outcomes, including physical and psychological damage to people, as well as disruptions to communities' social and economic systems. It is essential to address the underlying reasons of internal displacement and put effective techniques for risk reduction, early warning, and reaction into place if one want to forestall its occurrence. This may involve actions such as resolving conflicts, managing the risks of natural disasters, and using community-based ways to meeting the needs of people who have been displaced inside their own country. This study posits that there is also a need for an improved level of dedication and cooperation on the part of the government, in addition to help from international organisations, in order to solve the problem of internal displacement in Nigeria.